2022
DOI: 10.3390/vaccines10111805
|View full text |Cite
|
Sign up to set email alerts
|

Plant Molecular Pharming and Plant-Derived Compounds towards Generation of Vaccines and Therapeutics against Coronaviruses

Abstract: The current century has witnessed infections of pandemic proportions caused by Coronaviruses (CoV) including severe acute respiratory syndrome-related CoV (SARS-CoV), Middle East respiratory syndrome-related CoV (MERS-CoV) and the recently identified SARS-CoV2. Significantly, the SARS-CoV2 outbreak, declared a pandemic in early 2020, has wreaked devastation and imposed intense pressure on medical establishments world-wide in a short time period by spreading at a rapid pace, resulting in high morbidity and mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 300 publications
0
2
0
Order By: Relevance
“…Physicochemical techniques are used to create green synthetic metal NPs. [ 31 ] Because there are many phytochemical components in plant extract, which may also function as reducing and stabilizing agents when converting metal ions into metal NPs, [ 32 ] as shown in Figure 3, the process of producing NPs from plant extract is inexpensive and has a high yield. Researchers have found that green synthesized NPs are more pharmacologically active than other methods.…”
Section: Green Synthesis Of Metallic Npsmentioning
confidence: 99%
“…Physicochemical techniques are used to create green synthetic metal NPs. [ 31 ] Because there are many phytochemical components in plant extract, which may also function as reducing and stabilizing agents when converting metal ions into metal NPs, [ 32 ] as shown in Figure 3, the process of producing NPs from plant extract is inexpensive and has a high yield. Researchers have found that green synthesized NPs are more pharmacologically active than other methods.…”
Section: Green Synthesis Of Metallic Npsmentioning
confidence: 99%
“…For instance, Medicago Inc., a company utilizing plant-based transient expression systems, can produce the purified end-product of an influenza vaccine just three weeks after receiving the sequence (D'Aoust et al, 2008). Most recently, Medicago Inc. demonstrated the capability of using transient systems for the production of a vaccine against SARS-CoV-2 and influenza (Venkataraman, 2022). The data demonstrated consistent immunogenicity in human clinical trials (Ward et al, 2021).…”
Section: Transient Expression Systemsmentioning
confidence: 99%
“…Metallic nanoparticles are synthesized via chemical and physical methods like solid state, sol-gel, ultrasonic irradiation, hydrothermal, microwave, etc Recently, researchers have been focusing on green synthesis methods because of many disadvantages of physical and chemical processes, such as more energy consumption, uses of hazardous chemicals, and generation of heterogenous NPs. Many studies have reported that due to the many phytochemicals (phenolics, terpenoids, etc), plant extract can act as a reducing and stabilizing agent by converting metal salt into nano form [16,17]. There are many studies reported synthesis of metallic nanoparticles using plants extract of jasmine flower [18], papaya [19], Piper nigrum, Coriandrum sativum, Syzygium aromaticum [20], rosemary, ginger [21], Impatiens rothii [22], Terenna asiatica [23], Garcinia mangostana [24], Iranian propolis [25], mango [26].…”
Section: Introductionmentioning
confidence: 99%